(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The main aim of this Project work is to reduce the pollution of rivers which are dumped with high amount of sewages, factory wastes, etc. Govt of India has made huge investments in various river cleaning projects. Nowadays most of the manufacturing process is being automated so as to deliver the products at a faster rate. Automation plays a vital role in production. In this project we’ve fabricated the remote operated river cleaning machine, the primary aim of the project is to cut back the the manpower, time consumption for cleaning the river. Here we’ve automated the functioning of river waste cleaning with the assistance of a motor and conveyor drive arrangement. Here hc-5 Bluetooth module provide to control the cleaning machine.